Pathogenic Deletion in the CLCNKB Gene in Parents of a Double First-Cousin Consanguineous Marriage: Bartter Syndrome with Delayed Diagnosis and Fatal Renal Outcomes in Two Siblings- a Case Report - Al- Makramani, Ali A (Journal of Neonatal Surgery, 2025)
The uncommon Bartter syndrome (BS) type III (classic) results from chloride voltage-gated channel Kb (CLCNKB) gene mutations affecting the chloride channel ClC-Kb in the kidneys' distal tubules. Nephrocalcinosis, premature birth, failure to thrive, and early-onset maternal polyhydramnios can or cannot manifest as their symptoms. We present the unique, rare, and novel case of type III BS associated with consanguineous parents (double first cousins) of two children [male 7.5 years, female 4 months] with a fatal outcome [mortality due to end-stage renal failure]. The male patient is also the first case with Type III BS that has been followed up for such a long time. Antenatal polyhydramnios was associated in both cases. The two siblings had different courses of their clinical presentations, signs, symptoms, and complications. Observations at different times revealed metabolic alkalosis, growth retardation, hypokalemia, hyponatremia, hypochloremia, anemia, hepatomegaly, superinfections, and high levels of serum bicarbonates. After their death, the CP was advised to undergo genetic counseling, which recommended preimplantation genetic diagnosis, which they willingly agreed to and are currently in the process of preparing for.